Reduction of beat frequency oscillation in a sliding mode controlled multi-phase voltage regulator module - Magsino, Jessica C. Cabiles
Voltage regulator modules are expected to be stable at both static and dynamic loading conditions. Unlike ordinary power supplies, voltage regulator modules (VRMs) are subjected to repetitive high frequency loading conditions depending on the software being run on the processor. However, when the transient load frequency is near the switching frequency of the VRM, high magnitude low frequency oscillations, known as beat frequency oscillations, are observed at the phase currents.In this study, sliding mode control is applied to both the voltage loop and the current share loop of the VRM with the aim of reducing the beat frequency oscillation in the phase currents of the module. Derivation for the fixed frequency sliding mode control was done in the analog domain and transformed into the digital domain using Direct Z-transform. A simulation model was developed for both the analog and the digital control implementations. Results show that compared to the analog sliding mode control implementation, beat frequency oscillation is eliminated in its digital counterpart, while maintaining equal load sharing among the modules.